2013
DOI: 10.1371/journal.pone.0080458
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Rare Circulating Tumor Cells in Non-Small Cell Lung Cancer by Ligand-Targeted PCR

Abstract: BackgroundQuantification of circulating tumor cells (CTC) is valuable for evaluation of non-small cell lung cancer (NSCLC). The sensitivity of current methods constrains their use to detect rare CTCs in early stage. Here we evaluate a novel method, ligand-targeted polymerase chain reaction (LT-PCR), that can detect rare CTCs in NSCLC patients.MethodsCTCs were enriched by immunomagnetic depletion of leukocytes and then labeled by a conjugate of a tumor-specific ligand and an oligonucleotide. After washing off f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 43 publications
5
85
1
Order By: Relevance
“…All patient samples were tested in duplicates with six standards and three quality controls. The observed CTC counts were computed as previously described [17].…”
Section: Ctc Enrichment and Quantitationmentioning
confidence: 99%
“…All patient samples were tested in duplicates with six standards and three quality controls. The observed CTC counts were computed as previously described [17].…”
Section: Ctc Enrichment and Quantitationmentioning
confidence: 99%
“…The LT-PCR-FOLR1 method has been investigated for detection of CTCs in NSCLC in several trials (22). The sensitivity of this method was applied to detect rare CTCs in early stage NSCLC patients.…”
Section: Detection Of Circulating Tumor Cells (Ctcs) In Non-small Celmentioning
confidence: 99%
“…The latter utilized differential expression of folate receptor on cell surface of cell types present in the sample: unlike blood cells, lung cancer cells tend to abundantly express folate receptor on their surface. This allowed previously-established average concentration of folate receptor per tumor cell (16) to be used to design a calibrator curve and to infer from the fluorescence detected in the quantitative PCR for folate receptor CTCs (expressed as CTC unit) how many were present in each sample. Remarkably, the number of CTC units detected corresponded tightly to the stage of NSCLC.…”
mentioning
confidence: 99%
“…While Tanaka's study discriminated between stage I and stage IV disease using CellSearch (9), Lou showed that CTC number correlated with stage I/II versus stage III and stage IV disease (16). With the technique used in their study, Wan and colleagues achieved even further distinction between stages by CTC number, being able to clearly determine CTC unit cut-offs delineating even stage I from stage II, in addition to being able to distinguish stage III and IV (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation